2017
DOI: 10.1136/thoraxjnl-2016-208846
|View full text |Cite
|
Sign up to set email alerts
|

Deficient retinoid-driven angiogenesis may contribute to failure of adult human lung regeneration in emphysema

Abstract: RA regulates lung microvascular angiogenesis; the endothelium produces CYP26A1 which is increased in emphysema, possibly leading to reduced RA availability. These data highlight a role for RA in maintenance of the human pulmonary microvascular endothelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 55 publications
1
21
0
1
Order By: Relevance
“…On the contrary, degradation of endogenous RA by increased CYP26A1, which occurs in emphysema, impairs endothelial cell repair and may contribute to chronic lung disease. This supports the clinical importance of maintaining an adequate vitamin A status for the conservation of lung function in humans [ 168 ].…”
Section: Vitamin a Deficiency And The Lungsupporting
confidence: 72%
“…On the contrary, degradation of endogenous RA by increased CYP26A1, which occurs in emphysema, impairs endothelial cell repair and may contribute to chronic lung disease. This supports the clinical importance of maintaining an adequate vitamin A status for the conservation of lung function in humans [ 168 ].…”
Section: Vitamin a Deficiency And The Lungsupporting
confidence: 72%
“…Studies in mice revealed that RA is a critical regulator of both embryonic lung development and post-natal alveolarization [ [15] , [16] , [17] , [18] , [19] ]. In vitro , ATRA stimulated human lung microvascular angiogenesis [ 20 ] and induced lung fibroblast elastin synthesis [ 21 ]. In man, epidemiological evidence revealed associations between vitamin A deficiency and reduced lung function in children that was alleviated by maternal vitamin A supplementation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…LIFs generate all-trans retinoic acid (ATRA) that acts autocrinally to upregulate elastin gene expression and synthesis, thus playing a crucial role in the induction of septal eruption [116,119,120]. Moreover, ATRA acts paracrinally to induce proliferation of the adjacent AEC2 [121,122], gene expression [115], and angiogenesis in microvascular endothelial cells [123]. After birth, esters start to disappear from the lung and are converted into active forms, like retinol and RA [98,104,124].…”
Section: Alveolar Phasementioning
confidence: 99%
“…Moreover, and considering retinoic acid role in the later phases, RA might be a suitable candidate to improve some chronic diseases in the adult by promoting regenerating/repair events. rarα −/− (↓ alveolar number and surface area) rarβ −/− (early & faster septation; ↓ surface area) rarγ −/− (↓ elastic tissue, ↓ alveoli number, ↑ distance between the alveolar walls) rxrα −/− (embryonic lethality) rarγ −/− , rxrα +/− (↓ elastic tissue at the alveolar septa) [88,94,97,104,[107][108][109][110][111][112]123,126,127,130,134] ↓, decrease; ↑, increase.…”
Section: Final Remarksmentioning
confidence: 99%